Behavior of solutes and membrane fouling in an electrodialysis to treat a side-stream: Migration of ions, dissolved organics and micropollutants - An Byung Min; SHINE LIN AUNG; 최지혁; 차호영; 조진수; Byambaa Battuya; Song, Kyung Guen (Elsevier BV, 2023)
The electrodialysis (ED) is widely applied as a reliable low-energy process in which ions are transferred through selective ion-exchange membranes. The purpose of this study is to confirm the efficiency of the ED system for removing nutrient ions contained in the side-stream of actual wastewater and to identify the propensity of ion exchange membrane fouling by dissolved organic matter and micropollutants contained in the side-stream. As a result of the constant-voltage of 7 batch operation for the side-stream, 92.1 % of ammonium and 52.4 % of phosphate were removed, and it was confirmed that the ED system was particularly effective in removing ammonium. The propensity of the membrane fouling by organic solutes was compared by measuring elemental analysis and FTIR spectra of three types of ion-exchange membranes: original, fouled, and cleaned. It was confirmed that low-molecular-weight organic matter was an important cause of organic fouling, and SEM-EDS analysis showed that acid-base cleaning is effective in removing organic foulants. Among the remaining micropollutants, diclofenac, gemfibrozil, ibuprofen, ketoprofen, and naproxen can be removed by the ED system according to their ionic characteristics, but some of the diclofenac and gemfibrozil are presumed to be adsorbed on the membrane due to their hydrophobicity.